2002
DOI: 10.1128/aac.46.4.1073-1079.2002
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Polyamines and Bacterial Outer Membranes as Investigated with Ion-Selective Electrodes

Abstract: We analyzed the interaction between polyamines and the outer membrane of Escherichia coli cells using potentiometric measurements with Ca 2؉ , tetraphenylphosphonium (TPP ؉ ), and K ؉ electrodes. The Ca 2؉electrode was used to examine the ability of the polyamines to release Ca 2؉ from the outer membrane. The TPP ؉ electrode was used to examine the ability to permeabilize the outer membrane, since the uptake of TPP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 27 publications
0
51
0
Order By: Relevance
“…Although required, the cationic charge is not sufficient per se to cause either the permeabilisation of bacterial membranes or the bacteria killing (Katsu et al, 2002;Savage et al, 2002). In fact, the hydrophobic moiety of CAAs is responsible for their insertion into the hydrophobic core of the bacterial lipid bilayer, leading to membrane permeabilisation and eventually to CAAs-mediated bacterial killing as convincingly indicated by the lack of membrane permeabilisation of a deacylated polymyxin analogue (Vaara and Vaara, 1983;Tsubery et al, 2000Tsubery et al, , 2001Tsubery et al, , 2002Katz et al, 2003;Clausell et al, 2005Clausell et al, , 2007.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Although required, the cationic charge is not sufficient per se to cause either the permeabilisation of bacterial membranes or the bacteria killing (Katsu et al, 2002;Savage et al, 2002). In fact, the hydrophobic moiety of CAAs is responsible for their insertion into the hydrophobic core of the bacterial lipid bilayer, leading to membrane permeabilisation and eventually to CAAs-mediated bacterial killing as convincingly indicated by the lack of membrane permeabilisation of a deacylated polymyxin analogue (Vaara and Vaara, 1983;Tsubery et al, 2000Tsubery et al, , 2001Tsubery et al, , 2002Katz et al, 2003;Clausell et al, 2005Clausell et al, , 2007.…”
Section: Introductionmentioning
confidence: 97%
“…Whereas the interaction of other CAAs with biological membranes has been the subject of numerous studies, particularly with polymyxin B (PMB) (Chen and Feingold, 1972;Clausell et al, 2004Clausell et al, , 2005Clausell et al, , 2007Hartmann et al, 1978;Katsu et al, 1984Katsu et al, , 2002Katz et al, 2003;Galla, 1981, 1982;Tsubery et al, 2000Tsubery et al, , 2001Tsubery et al, , 2002Wiese et al, 1998Wiese et al, , 2003, relatively little information is available regarding the interaction of SQ with cellular membranes (Chen et al, 2006;Salmi et al, 2008a;Selinsky et al, 1998Selinsky et al, , 2000.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Katsu et al 63 reported that the outer membrane of gramnegative bacteria prevents the penetration of hydrophobic antibiotics into cells. Hence, the cationic compounds are used to enhance the permeability of the outer membrane and thereby increase the sensitivity of gram-negative bacteria to several antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…The TPP ϩ electrode was constructed as reported previously. 25) The E. coli cells harboring recombinant plasmids were grown in Tanaka medium supplemented with 1% tryptone, 20 mM potassium lactate and 10 mg/ml of chloramphenicol at 37°C until OD 650 of 0.5. The cells were harvested and washed 3 times with 0.1 M MOPS-KOH, pH 7.0.…”
Section: Tppmentioning
confidence: 99%